Sistem Informasi Pelayanan Kesehatan Dalam Meningkatkan Mutu Pelayanan Klinik As-Syifa Bengkulu Berbasis Web: Sistem Informasi Pelayanan Kesehatan Dalam Meningkatkan Mutu Pelayanan Klinik As-Syifa Bengkulu Berbasis Web - Surya Ade Saputera; Nurul Chotimah; Gunawan (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
Abstract— Asy-Syifa Clinic is a Primary Health Care Clinic for BPJS Health Bengkulu, which is located at Jl. BengkuluFlamboyant. At the Asy-Syifa Bengkulu clinic, health services such as patient registration and poly practice schedulesare still carried out by means of patients having to come directly to the clinic or by telephone, then patients who want todo health consultations often experience disappointment, because the clinic they want to meet does not come to practiceand do not know the exact consultation schedule information for patients. The purpose of this study is to make it easierfor the Asy-Syifa clinic to provide patientregistration information and poly practice schedules to patients and to improvethe health service facilities of the Asy-Syifa Bengkulu clinic. The system development method uses Rapid ApplicationDevelopment (RAD), system design using DFD (Data Flow Diagram). This study has produced a health serviceinformation system at the Asy-Syifa clinic Bengkulu with 2 users, namely admin and patient.Keywords— Asy-Syifa Clinic, Health Services, RAD, Data Flow diagram(DFD)